A surveillance analysis of case findings in the prevention and control of pneumonia in children under five years old: a literature review - Rini Fortina; Chatarina U.W; Suyuti Syamsul; Cresti S.S; Riyanti Riyanti (AOSIS, 2023)
Background: Pneumonia is one of the leading causes of death in children under 5 years of age. Although overall deaths from pneumonia have decreased substantially by 56%, since 1990 pneumonia contributes to about 740,000 deaths, per year. In Indonesia, in 2021, 444 children under five (CFR 0.16%) died due to pneumonia, in 2020, 498 children under five (CFR 0.16%), and in 2019, 551 children under five (CFR 0.12%). Increasing the scope of finding pneumonia in children under five is one of the efforts done in Indonesia to control pneumonia. The Influenza Like Illness and Severity Acute Respiratory System (ILI-SARI) surveillance is sentinel surveillance that is used to catch cases of pneumonia under five in outpatient and inpatient health facilities. Objective: This literature review aims to describe the implementation of ILI-SARI surveillance increasing the detection of pneumonia in children under five. Methods: The method used is to search the database through Google Scholar, Pubmed, and Research Gate. The key words used in this database search were ILI-SARI surveillance, Pneumonia under five. Results:  There are 8 articles obtained and 5 articles analyzed through the suitability of the topic, objectives, methods used, sample size, and results from each article. Conclusion: Care-seeking activities are suggested to be an integral part of this method of preventing and controlling under-five pneumonia.